Effects of straw incorporation and potassium fertilizer on crop yields, soil organic carbon, and active carbon in the rice–wheat system - Yuan, Guoyin; Huan, Weiwei; Song, Hang; Lu, Dianjun; Chen, Xiaoqin; Wang, Huoyan; Zhou, Jianmin (Soil & tillage research, 2021)
•Soil organic C and active C fractions were compared in organic and inorganic K source.•Straw returning increased SOC than inorganic K via increasing active C contents.•Straw incorporation increased yield more in wheat than rice over without K fertilizer. Active soil organic carbon (SOC) fractions play a key role in agricultural soil fertility. However, the effects of potassium application and straw incorporation on SOC and active SOC fractions as well as the relationships among these factors in a rice–wheat system are less well-studied. Hence, the objective of this study was to analyse the effects of potassium fertilization and straw incorporation on SOC sequestration, active carbon fractions, and crop yields in a long-term (6 years) field experiment. Four treatments were examined: no addition of potassium fertilizer and straw (CK), straw incorporation only (SI), potassium-fertilizer application only (K), and straw incorporation plus a recommended amount of potassium fertilizer (SI + K). SOC, dissolved organic carbon (DOC), light fraction organic carbon (LFOC), microbial biomass carbon (MBC), easily oxidizable carbon (EOC), crop yields, and the carbon pool management index (CMI) were determined. After 6 years, SOC content and labile C fractions in the SI treatment increased significantly, by 7.95–25.0 % and 23.6–185 %, respectively, compared to the CK treatment. Significant and positive correlations were observed between SOC, DOC, LFOC, MBC, EOC, and the CMI (r = 0.449–0.899, P < 0.01). Among the five C fractions, LFOC, DOC, and EOC were the most sensitive indicators of changes in SOC induced by incorporating straw with or without potassium fertilizer. The highest SOC contents and labile C fractions were observed in the SI + K treatment. Rice yields increased from 8.55 and 7.59 t ha−1 in the CK plots to 9.56 and 8.54 t ha−1 with SI + K at Guangde (GD) and Jiangyan (JY) sites, respectively. Wheat yields increased from 0.53 and 5.33 t ha−1 in the CK plots to 5.86 and 6.43 t ha−1 with SI + K at GD and JY sites, respectively. Overall, based on crop yields and C storage, straw incorporation in combination with a moderate amount of potassium fertilizer appears to be the best practice for improving soil fertility and productivity in the rice-wheat cropping system.